Trade policies and food security: Essays from IFPRI's 2002-2003 Annual Report - Watkins, Kevin; von Braun, Joachim; Díaz-Bonilla, Eugenio; Gulati, Ashok (International Food Policy Research Institute, 2003)
Globalization could and should benefit developing countries. But unlike a rising tide that lifts all boats, large and small, globalization is unequal. It has fallen far short of its much-ballyhooed potential to help the world’s poorest people out of poverty. Instead, a combination of policies in both rich and poor countries creates conditions for the rich to prosper and many of the poor to fall more deeply into destitution. Agricultural protectionism in rich countries enables them to skew markets in their favor. Tariffs and trade barriers routinely exclude developing-country products. Other non-tariff barriers, such as non-transparent phytosanitary regulations, present additional impediments to poor farmers seeking to enter the global marketplace. Instead of distorting the marketplace, rich nations must pay more than lip service to the ideal of free and fair trade. The World Trade Organization (WTO) is the arena to do so internationally. Public policies in developing countries also harm poor farmers and producers, who often lack the basic conditions for prosperity: health, education, land, capital, information, and the marketing infrastructure needed to take advantage of export opportunities. Developing-country governments can and must change domestic policies on markets, land tenure, research and extension, and credit to enable smallholder farmers to compete. The two feature essays in this year’s annual report examine who must do what in order for agricultural globalization to work for the poor. Unilateral measures by one side or the other will help. But only concerted effort by both developed- and developing-country governments and institutions to change trade rules, regulations, and practices will enable the very poor to feed their families and live a better life.